The Effect Of Gold Price Fluctuation On Gold Paid Products On The Profitability Of Mandiri Sharia Bank For The 2017 – 2019 Period - Ahmad Lutfi Ahmad Lutfi; Erpi Rahman; Nining Kurniasih (Journal of Business, Accounting and Finance, 2020)
This study has an effect on fluctuations in the price of gold on the profitability of Bank Syariah Mandiri's 2017-2019 gold pawn products. The purpose of this study was to determine the effect of gold price fluctuations on gold pawn products on the profitability of Bank Syariah Mandiri 2017-2019. The research method used in this study is a quantitative research method with a descriptive approach with a sample size of 36 data. Methods of data collection using documentation, literature study and internet studies and data processing using SPSS 25. The results showed the results of the coefficient of determination test obtained the t regression model with a correlation coefficient R of 0.073, the value of the coefficient of determination R Square was 0.005. This means that the magnitude of the influence of the independent variables on the variation of variable changes is 0.05%. This shows that this study has a coefficient of determination of 0.05% while the remaining 99.95% is influenced by other variables used in this study. The results of hypothesis testing found fluctuations that the price of gold in gold pawn products had no significant effect on profitability. This is indicated by the value of t count is smaller than tta table (0.425 < 2.03) and the significance value is greater than 0.05 (0.674 > 0.05).